Treatment of overactive KATP channels with glibenclamide in a zebrafish model and a clinical trial in humans with Cantú syndrome - Lotte Kleinendorst; Sarah E. Siegelaar; Helen I. Roessler; Lema Meiwand; Malou van den Boogaard; Rianne H.A.C.M. de Bruin-Bon; Kirsten F. van Duinen; R. Nils Planken; Elisabeth H. Jaspars; Patrick M.J.H. Kemperman; Berto J. Bouma; Colin G. Nichols; et al. (Scientific Reports)
Abstract This study explores the efficacy of glibenclamide, a KATP channel inhibitor, for treating Cantú syndrome (CS), a genetic disorder characterized by hypertrichosis and cardiovascular abnormalities. Treatment with glibenclamide for Cantú syndrome has only been reported in a single case report. In this study, we tested this repurposed drug in both a zebrafish model and an open-label trial with CS patients. CS zebrafish embryos, created using CRISPR/Cas9, were treated with glibenclamide. Their cardiac function was assessed using high-speed imaging. In the trial part of the study, four adults with CS used 2.5 mg glibenclamide daily for 8 months. Hypertrichosis, cardiac function, and edema were evaluated and glucose levels were monitored continuously. In the zebrafish model of CS glibenclamide reversed cardiac abnormalities. However, in the clinical trial, the effects on hypertrichosis were mixed, and there were no significant changes in cardiac phenotype or leg edema. One participant reported reduced facial erythema and puffiness, which relapsed post-trial. The treatment was generally safe, with multiple instances of level 1 hypoglycemia but no severe adverse events. In conclusion, glibenclamide can reverse cardiac abnormalities in a CS zebrafish model. Its effect on hypertrichosis and cardiovascular features in humans with CS are unclear and dosage increases are challenging due to hypoglycemia, which is important knowledge for treatment considerations in this rare genetic syndrome. Trial registration: EudraCT Number 2019-004651-36. Date of first registration 21/05/2021.